Brand Experience and Customer Loyalty in Dentistry: The Role of Perceived Brand Authenticity - Ghaith Al-Abdallah; Jegr Ababakr (Hindawi Limited, 2023)
This study investigates the impact of brand experience (BE) on customer loyalty (CL) and examines the possible mediating effect of brand authenticity (BA) and the moderating effect of frequency of visits on the original relationship between BE and CL in dental practices. A descriptive, deductive, and quantitative research methodology was applied, with a self-administrated survey questionnaire over a cross-sectional convenience sample from dental clinics and centers in Erbil, Sulaymaniyah, and Duhok (Iraqi Kurdistan). Data were collected in July and August 2022. SPSS AMOS 26 was used for analyzing 952 patients' responses. The results indicate that BE has a statistically significant positive effect on CL. However, only affective experiences, cognitive experiences, and behavioral experiences have a statistically positive effect on CL. BA has a significant direct mediation effect on the original relationship between BE and CL. In addition, a greater frequency of dental visits improves the BE and impacts CL. Discussion, recommendations, and future research orientation are provided.